1992
DOI: 10.1159/000227013
|View full text |Cite
|
Sign up to set email alerts
|

Homotypic Aggregation and Terminal Glycosylation of Cells from Dissociated Human Colorectal Tumor Tissue

Abstract: Colorectal tumor tissue directly obtained from the surgeon was dissociated by enzymatical and mechanical disruption into a suspension of single cells of high viability. Homotypic aggregation, sialidase-accessible sialic acid and total fucose content of tumor cells were determined. Aggregation of cells from mucinous tumors was found to be significantly lower than of cells from nonmucinous tissue. The median value of surface-bound sialic acid was lower in strongly aggregating cells compared to nonaggregating cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…A similar finding was previously described by Kemmer et al [9], working with cells isolated from human colorectal adenocarcinomas. Considering all these results and our present observation on AAA reactivity, we can assume that in colorectal tumors, there may be an increased occurrence of fucose residues bound with linkages other than · (1,6).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A similar finding was previously described by Kemmer et al [9], working with cells isolated from human colorectal adenocarcinomas. Considering all these results and our present observation on AAA reactivity, we can assume that in colorectal tumors, there may be an increased occurrence of fucose residues bound with linkages other than · (1,6).…”
Section: Discussionsupporting
confidence: 88%
“…Biochemical, histochemical and immunohistochemical studies have demonstrated differences between the glycoconjugates of normal and cancerous colorectal mucosa [5][6][7]. In this respect, changes in sialylation and fucosylation have been reported in malignant colorectal tumors and appear to be of great significance for the invasiveness and metastatic potential of tumoral cells [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…A large amount of membrane-bound sialic acid promotes invasion [1,2], interferes with intercellular adhesion of freshly isolated colorectal carcinoma cells from surgical specimens [3], and stimulates platelet-aggregating to glycoproteins or glycolipids. For the synthesis of all known sialo-oligosaccharides, 10-12 sialyltransferases are necessary, some of which have been cloned successfully [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of sialic acid at the terminal or near the terminal position underlies its importance in determining chemical and biological diversity, and characteristics of cell-surface and secreted glycoproteins [6]. Human and experimental model based studies have documented clinical significance of this sugar moiety [7,8]. Numerous investigators have reported possible relation of increased sialic acid levels with various malignancies [9][10][11].…”
mentioning
confidence: 99%